Clinical studies of phytogel "Kvertulidon" stomatoprotective action in patients with helicobacter gastritis - O. E. Uspensky; P. I. Pustovoit (Kazimierz Wielki University, 2019)
Background. To determine the therapeutic and prophylactic effect of oral applications of the Kvertulidon phytogel on the condition of the oral cavity in patients with Helicobacter gastritis. Methods. A total of 28 patients with a diagnosis of gastritis of Helicobacter pylori and 18 healthy individuals were surveyed. Phytogel was used as oral applications for 15 days. Hygiene and dental indices were determined, and the level of biochemical markers of inflammation, dystrophy and defenses in the oral fluid: elastase, catalase, urease, lysozyme activity, MDA content, API index and degree of dysbiosis. Results. A significant increase in all hygienic and dental indices was found in patients with gastritis with a decrease in the level of catalase and lysozyme. Applications of phytogel reduce the activity of elastase, urease, the content of MDA, the degree of dysbiosis and increase the activity of catalase, lysozyme, and the API index. Conclusion. Phytogel "Kvertulidon" has stomatoprotective effect in patients with helicobacter gastritis.